Sensory curation: theorizing media use for sensory regulation and implications for family media conflict. Issue 4 (4th July 2019) - Harrison, Kristen; Vallina, Lia; Couture, Amelia; Wenhold, Halie; Moorman, Jessica D.
ABSTRACT: Media sensory curation theory, introduced here, complements theories of informational, emotional, and relational media gratifications. Sensory curation theory conceptualizes media devices as tools people use to help maintain sensory regulation by simultaneously capturing and curbing sensory input within built and natural environments. This article explicates the theory and introduces the Child and Adult Media Sensory Curation Inventories (MediaSCIs), separate measures of child and adult media sensory behaviors and preferences. A survey of 789 parents and adult caregivers of children ages 3 to 14 revealed moderate to strong correlations between general sensory processing and media sensory curation, validating the MediaSCIs. Controlling usage time, child media sensory curation strongly predicted problematic child media use and moderately predicted adult–child media conflict, which was four times as frequent among adult–child pairs with high MediaSCI scores than with low MediaSCI scores.